2016
DOI: 10.2147/idr.s113861
|View full text |Cite
|
Sign up to set email alerts
|

Assessing parasite clearance during uncomplicated <em>Plasmodium falciparum </em>infection treated with artesunate monotherapy in Suriname

Abstract: BackgroundArtemisinin resistance in Plasmodium falciparum is suspected when the day 3 parasitemia is >10% when treated with artemisinin-based combination therapy or if >10% of patients treated with artemisinin-based combination therapy or artesunate monotherapy harbored parasites with half-lives ≥5 hours. Hence, a single-arm prospective efficacy trial was conducted in Suriname for uncomplicated P. falciparum infection treated with artesunate-based monotherapy for 3 days assessing day 3 parasitemia, treatment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…Studies conducted in Western Cambodgia on artemisinin alone have reported 84 hours for PCT which was related to artemisinin resistance. 12 , 32 , 33 The PCT with artemisinin observed in African patients is therefore much lower than that found in Western Cambodia. 34 …”
Section: Discussionmentioning
confidence: 73%
“…Studies conducted in Western Cambodgia on artemisinin alone have reported 84 hours for PCT which was related to artemisinin resistance. 12 , 32 , 33 The PCT with artemisinin observed in African patients is therefore much lower than that found in Western Cambodia. 34 …”
Section: Discussionmentioning
confidence: 73%
“…To further investigate this possibility, from July 2013 until July 2014, a TES consisting of 3 days of artesunate monotherapy followed by mefloquine and primaquine was conducted in Suriname to determine the efficacy of artemisinin, without confounding partner drugs. In that study, the day 3 positivity rate for P. falciparum was 10%, and at least 17.9% of the samples exhibited a parasite half-life of Ն5 h, suggesting suspected partial artemisinin resistance (24).…”
mentioning
confidence: 75%
“…An in vivo efficacy study conducted in 2011 demonstrated that 31% of P. falciparum -infected patients, treated with Coartem ® were still positive on day 3 [ 2 ]. An in vivo efficacy study in 2014 with artesunate further revealed that at least 17.9% of samples exhibited a parasite half-life ≥ 5 h [ 3 ]. Molecular characterizations of drug-associated markers of isolates from Suriname did not reveal noteworthy alterations in potential molecular markers in the pfATP6 [ 4 ], pfmdr1 [ 5 ] and K13 genes [ 6 ], but increased pfmdr1 copy numbers in P. falciparum isolates [ 7 ] have been observed.…”
Section: Introductionmentioning
confidence: 99%